Pemanfaatan Media Digital sebagai Pendidikan Komunikasi Pemasaran dalam Meningkatkan Kreativitas Promosi Produk UMKM - Wiratri Anindhita; Kinkin Yuliaty Subarsa Putri; Dwi Linda Kusuma; Khoirul Muttaqin (Journal of Management and Bussines (JOMB), 2024)
This research aims to identify and analyze the mastery of marketing communications through digital media in increasing the creativity of MSME product promotions. This research involved five MSME actors in Jatinegara Kaum, East Jakarta, and used a qualitative approach with data collection techniques in the form of in-depth interviews and observations. The research results show that MSMEs mainly use social media Instagram and WhatsApp to market their products. In conclusion, the presence of digital media helps them introduce and market their products, as well as simplify the ordering process. However, there are supporting and inhibiting factors in the use of digital media. It is hoped that further research will be able to identify needs and design development programs that can overcome obstacles in digital-based marketing. Keywords: Instagram, Digital Media, Micro, Small and Medium Enterprises (MSMEs), Marketing, WhatsApp